Assessing the Effects of Metformin on Lipid Metabolism in Women with PCOS: Metformin on Lipid Metabolism in PCOS - Afridi, Sanodia; Saifullah, Shabina; Falah, Shaikh Fahad; Naz, Falak; Ahmad, Shafiq; Shaukat, Asma (Pakistan Journal of Health Sciences, 2025)
Polycystic ovary syndrome (PCOS) is a prevalent hormonal imbalance condition that is linked with insulin resistance and abnormal lipid metabolism. Metformin is a common drug given in the management of PCOS; the impact on the lipid profile and the role of adherence to therapy are not established. Objectives: To assess the therapeutic effects of Metformin on lipid profile, hormonal status, and insulin resistance in PCOS while exploring the influence of patient adherence on overall treatment response. Methods: One hundred and ten women with a diagnosis of PCOS in Health Net Hospital, Peshawar, were given Metformin (1500 mg/day) for six months. The assessments for the study included lipid profile, glucose, insulin level, HOMA-IR, and hormonal profiling both at baseline and after the treatment. Treatment adherence was evaluated with pill count and attendance to follow-up visits. Pre- and post-comparisons were done using paired t-tests, while group differences were examined using independent t-tests and chi-square tests. Results: Metformin significantly reduced total cholesterol (199.43 to 167.60 mg/dL, p<0.001), LDL-C (131.71 to 111.20 mg/dL, p<0.001), triglycerides (178.15 to 149.66 mg/dL, p<0.001), and VLDL-C (35.72 to 30.03 mg/dL, ‘p<0.001’), while HDL-C increased (39.70 to 45.24, p<0.001)’. Insulin resistance and androgen levels also improved, with greater benefits observed in adherent participants. Conclusions: It was concluded that metformin positively impacts lipid metabolism, hormonal levels, and insulin responsiveness in patients with PCOS. Adherence significantly enhances therapeutic outcomes, emphasizing the need for strategies that promote consistent medication use.